Investor Overconfident Dalam Penilaian Saham: Perspektif Gender Dalam Eksperimen Pasar - Kufepaksi , Mahatma (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2010)
This current experimental research is done to answer whether the male or female investors tend to be more overconfident in the capital market. There are thirty volunteers participate in this research. According to research design, all participants are classified into two groups based on their score of overconfidence, namely less informed investors, and more informed investors and each group will be analyzed based on the gender perspective. It employs three different types of treatments consisting of the state of no available market information, the guidance of prediction, and the signal of good news. The result demonstrates that male and female investors in the group of less informed investors perform the same level of overconfidence when there is no available market information. Meanwhile, in the group of more informed investors, male investors tend to be more overconfident than do female ones. After accessing the guidance of prediction, male investors in the group of the less and the more informed investors tend to be more overconfident than do the female investors. After receiving good news, female investors in the group of less informed investors tend to be more overconfident than do male ones, but in the group of more informed investors, both male and female investors perform the same level of overconfidence.